Quantum control of a model qubit based on a multi-layered quantum dot - Ferron, Alejandro (2013)
In this work we present a model qubit whose basis states are eigenstates of a multilayered quantum dot. We show that the proper design of the quantum dot results in qubit states that have excellent dynamical properties when a time-dependent driving is applied to it. In particular, it is shown that a simple sinusoidal driving is sufficient to obtain good quality Rabi oscillations between the qubit states. Moreover, the switching between states can be performed with very low leakage, even under offresonance conditions. In this sense, the quantum control of the qubit is robust under some perturbations and achieved with simple means. More precisely, in this article, we propose a device that is within the reach of current semiconductor technology, a ZnS/CdSe/ZnS/CdSe/ZnS layered quantum dot. In addition, in order to clarify, we show a more general and theoretical model, which we believe is helpful in order to search the ideal experimental device.